Upaya Meningkatkan Pemahaman Operasi Hitung Bilangan Dengan Metode Alat Peraga Matematika Kelas II di SDN 1 Cicapar - Erinawati; Dina Syaflita (Algebra: Journal of Matematics, Statistics and Computation, 2024)
This research is based on obtaining observational data which shows the learning outcomes of grade 2 students at SD Negeri 1 Cicapar in mathematics learning who have not achieved optimal goals as expected. In response to these findings, researchers carried out classroom action research with the aim of increasing students' understanding of learning. This research aims to determine the effect of using teaching aids on the understanding of number counting operations material for class II students at SDN 1 Cipapr. The research was carried out in class 2 of SDN 1 Cipapar with a total of 25 students. Data collection was carried out by observation and tests. The research results obtained show an increase in understanding in each cycle. Students' learning progress is in achieving good grades in cycle 1, getting an average score of 60 and an average score of 80 in cycle 2 with a completion percentage of 90%. The results of the above research using mathematics teaching aids can improve the understanding of number calculation operations for class II students at SDN 1 Cipapar.